4-Cyanopyridine, a versatile mono- and bidentate ligand. Crystal structures of related coordination polymers determined by X-ray powder diffraction. Issue 16 (6th April 2017) - Zhao, Haishuang; Bodach, Alexander; Heine, Miriam; Krysiak, Yasar; Glinnemann, Jürgen; Alig, Edith; Fink, Lothar; Schmidt, Martin U.
Abstract : 4-Cyanopyridine (4-CNpy) as a monodentate ligand in single or double chains or as a bidentate ligand in two-dimensional networks. Abstract : 4-Cyanopyridine (4-CNpy, also known as isonicotinonitrile) can act as a monodentate ligand in transition metal complexes via the pyridine nitrogen atom (Npy ), or as a bidentate ligand via both nitrogen atoms (Npy and NCN ), resulting in a linear bridge between two metal atoms. Seven new polymeric transition metal compounds, [CuCl2 (4-CNpy)] n (1b ), [MnCl2 (4-CNpy)] n (2b ), [NiCl2 (4-CNpy)2 ] n (3a ), [NiCl2 (4-CNpy)] n (3b ), [CoBr2 (4-CNpy)2 ] n (4a ), [NiBr2 (4-CNpy)2 ] n (5a ) and [NiBr2 (4-CNpy)] n (5b ), are reported. Compounds1b, 2b, 3b and5b were obtained from the corresponding [M(ii )X2 (4-CNpy)2 ] n compounds by careful thermal decomposition under controlled conditions. Compounds3a, 4a and5a were synthesized from 4-cyanopyridine and transition metal halides. For all compounds, IR-spectroscopy was used to distinguish between mono- or bi-coordination of the 4-cyanopyridine ligand: in bi-coordinated compounds the asymmetric stretching vibrations of the cyano group v as (CN) are shifted to higher frequencies. All crystal structures were determined from X-ray powder diffraction data. Compounds1b, 3a, 4a and5a consist of polymeric chains of octahedra (double chains for1b ; single chains for3a, 4a and5a ), in which 4-cyanopyridine acts as a monodentate ligand via the Npy atom. Compound1b exists in two polymorphs, a triclinic (α -1b ) and a monoclinic phase (β -1b ); both exhibit a strong Jahn–Teller distortion of the CuCl5 N-octahedra. On the other hand, 2b, 3b and5b exhibit layered structures, in which the 4-cyanopyridine acts as a bidentate ligand. Both nitrogen atoms coordinate to metal atoms, resulting in a linear M(ii )-py-CN–M(ii ) bridge. These are the first examples of Mn and Ni compounds in which two 3d metal atoms are connected by a 4-cyanopyridine bridge. Due to the linearity of this bridge, 4-cyanopyridine lends itself to the construction of new metal–organic frameworks.